Protection of Personal Data Information in Indonesia - Jonathan Brilliannata; Rofikotul Jamiilah; Haidar Talib (LEGAL BRIEF, 2022)
With the rapid development of technology at this time, causing us to have to register our personal data with many service providers (providers) to provide certainty of user data, so that we can enjoy their services. With this, it causes vulnerabilities for the leakage of our personal data information that is managed by these providers. It can be seen that the violations of personal data protection were caused either due to irresponsible use by the provider and also due to data breaches by irresponsible people (hacking). Leakage of personal data can occur because there are no laws and regulations that specifically regulate the regulations for protecting people's personal data. Therefore, the government must immediately discuss and finalize the Personal Data Protection Bill to minimize the occurrence of data leakage cases such as those that have occurred before so that they do not happen again. The conclusion of this scientific work is that there are already protections regulated in the laws and regulations in Indonesia, but all of these regulations have not explicitly regulated the protection of personal data. In addition, it is necessary to make special rules regarding Personal Data Protection in order to provide clarity and assurance regarding the protection of personal data. This can be done with the establishment of the Personal Data Protection Bill (RUU PDP).